PENGARUH CITRA MEREK DAN DESAIN PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPATU COMPASS - Raul Frida Putra; Neng Siti Komariah (Jurnal Ilmiah Akuntansi dan Manajemen, 2022)
This study aims to examine the influence of brand image and product design on purchasing decisions for Compass shoes. The provision of this sample uses purposive sampling with the Slovin formula to obtain 100 respondents, namely followers of social media Instagram Compass shoes. Hypothesis testing in this study using multiple linear regression analysis using IBM SPSS 26. The results of this study indicate that (1) brand image has a positive and significant effect on purchasing decisions for Compass shoes (2) product design has a positive and significant effect on purchasing decisions for Compass shoes (3) brand image and product design simultaneously have a simultaneous effect on purchasing decisions for Compass shoes.